Synthesis of Polyoxymethylene Dimethyl Ethers Catalyzed by Rare Earth Compounds - Shi, Gao-Feng; Miao, Jian; Wang, Guo-Ying; Su, Jin-Mei; Liu, Hai-Xiao (Asian Journal of Chemistry, 2015)
Polyoxymethylene dimethyl ethers (PODMEn) have been synthesized in moderate yields by the reaction of methylal (PODME1) and paraformaldehyde catalyzed by rare earth compounds. The activities of catalyst in the reaction were investigated and the results show that La3+/SO42- has a high value. The influencing factors of reaction such as catalyst amount, reaction temperature, time, pressure and mole ratio of methylal (PODME1) to paraformaldehyde were also investigated. The appropriate reaction conditions i.e., n(paraformaldehyde)/n(methylal) = 1.60, catalyst amount of 1 %, 130 °C, 6 h and 0.5 MPa. Under the above conditions, methylal conversion rate and selectivity of PODME2-8 is 81.6 and 75.5 %, respectively. In addition to, the combustion and emission characteristics of PODME2-8 added diesel was compared with the diesel, polyoxymethylene dimethyl ethers (PODME2-8) not only improved the combustion characteristics of diesel, but improved the low temperature fluidity.